Pelatihan Penentuan Dimensi dan Indikator Lingkungan Kerja Eksisting di Sekretariat Daerah Pemkot Kupang - Jefirstson Richset Riwukore (Penerbit Goodwood, 2022)
Purpose: To improve the ability of employees at the Regional Secretariat of the Kupang City Government in identifying and understanding the dimensions and indicators of the employee's work environment based on organizational needs which can later improve employee performance and productivity. Research methodology: The implementation of this community service activity uses a focus group discussion (FGD) technique which was previously carried out through the stages of the survey, problem identification and questionnaire distribution, training and design, final questionnaire distribution, and report generation. Results: To identified dimensions of the work environment that affect performance consisting of (1) dimensions of the physical work environment with indicators of work equipment/work facilities, lighting, air circulation, noise, color, humidity, technology, mechanical vibrations in the workplace work, unpleasant odors at work, decorations at work, music at work, sounds at work, security officers at work, buildings or buildings, places to rest, places of worship (prayer and places of worship), means of transportation, pollution/pollution, and cleanliness, and availability of advice on handling the spread of the Covid-19 pandemic; and (2) the dimensions of the non-physical work environment with indicators relating to relationships with superiors, relationships with colleagues, relationships with subordinates, security at work, opportunities for advancement, harmonious relationships, boredom, work fatigue, privacy from employees, work atmosphere, time work, body condition at work, work complaints, and communication; leaders pay attention to the means of preventing the spread of Covid-19. Limitations: The limitations of this activity are limited to the identification of dimensions and indicators of the work environment. It needs to be simplified and further tested in factorial analysis to obtain a simplification of indicators but still comprehensive. Contribution: the contribution of this activity as a scientific development of human resource management, especially the use of dimensions and indicators of work environment variables.